ANALISIS KESULITAN BELAJAR SISWA MATERI MEMBACA PEMAHAMAN CERITA LEGENDA BERBAHASA JAWA MENGGUNAKAN MODEL PEMBELAJARAN DARING - Saraswati, Tea Haninda; Waluyo, Budi; Rahadini, Astiana Ajeng (Universitas Sebelas Maret, 2020)
This study aims to describe learning difficulties, causal factors, and efforts to overcome learning difficulties experienced by students in understanding the legend text through the online model. This research is a qualitative descriptive research with a case study method. The sampling technique used was purposive sampling. Data collection techniques using interviews, observation, and document analysis. Data analysis technique used is an interactive analysis model with three stages, namely data reduction, data presentation, and verification. Data validity test used is triangulation of data sources and triangulation of techniques. The conclusion of this research is that it is difficult to identify the main idea of the reading, it is difficult to determine the type of story, it is difficult to determine the relationship between the story and real life, it is difficult to determine the intrinsic element of the reading. The factors that cause it come from students (internal) and outside students (external). The internal factors are that students are lazy and have no interest in learning, give up easily, are tired, and have no confidence. While the external factors are following friends, unstable network, lack of attention, and economic conditions. The efforts made were the material provided to be concise and interesting, giving a few assignments, opening a question and answer session to students, and the school providing home visit facilities for underprivileged students.